Bubble Map’ Untuk Pembelajaran ‘Adjective’ Bagi Siswa Sekolah Dasar Sebagai Pengenalan Lokasi Pariwisata Untuk Pengunjung Kawasan Teluk Tomini - Wardatul Jannah Husain , Sabrina; El Walidayni Kau, Magvirah (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
This service activity aims to improve children's English vocabulary, particularly adjectives, which will be useful later when describing tourist attractions around them. This may benefit children in promoting tourist destinations to visitors from other countries. Children will be taught to use simple English adjectives using the